High Urinary Cotinine Levels and Low Academic Performance of Elementary School Students in Families with Careless Smoking Habits - Ika Yustisia; Nurdiana Sari; Suryani Tawali; Mutmainah Arif; Sitti Ramliah (eJournal Kedokteran Indonesia, 2022)
Children are the most vulnerable age group to become passive smokers due to cigarette smoke exposure, especially from family members. In addition, children who smoke passively are at high risk of experiencing declined cognitive performance. This study investigated the effect of cigarette smoke exposure on urinary cotinine levels and its relationship with elementary school students’ academic performance. The observational study with a cross-sectional design was located in Pannampu Village, Tallo District, Kota Makassar. Interviews, collecting academic performance data, and measuring urinary cotinine levels using colorimetric techniques were carried out on elementary school students (n=77). This study found that 88.5% of students stated that they had family members who smoked at home with inappropriate habits of exposing children to cigarette smoke. Urinary cotinine levels showed an average of 121.64 ng/mL. All students with urinary cotinine levels above 200 ng/mL (16.4%) had smoker family members. The urinary cotinine levels in boys were higher (p=0.014) with lower report card average marks than in girls. The smoking habits of family members were still a concern and had not protected children from cigarette smoke exposure, as evidenced by the high average urinary cotinine levels, especially in boys, which might affect their academic performance